Phish Defender: Real-Time Detection Of Phishing Websites Using A Browser Extension - Shyni, S. Adolphine; Harish, A.; Karthikeyan, P.; Zerro, S. Willfard Austen; Yogesh, R. (Metallurgical and Materials Engineering, 2025)
Phishing attacks are a major cyber security threat, helping users to disclose sensitive information through misleading websites that affect reliable sources. This paper presents the Phishdefender, which is a real -time phishing detection system that has been applied as a browser extension. The system examines henuristic analysis, URL structural inspection, material filtering and domain reputation to identify and respond to suspicious websites. Once a possible fishing attempt is discovered, the extension consumes the user with a warning banner and later redesigned them to a safe interface from the malicious site. Unlike traditional systems, which rely on heavy computational models, the Phishdefender provides a mild, skilled and user friendly solution that ensures active safety during everyday browsing. Experimental assessment displays its high identification accuracy and accountability, making it a practical tool to increase user safety in real -world landscapes.